2020
DOI: 10.1364/oe.405172
|View full text |Cite
|
Sign up to set email alerts
|

Temperature evaluation of colloidal nanoparticles by the thermal lens technique

Abstract: The use of highly sensitive thermometric methods is essential for the evaluation of nanoplatforms for photothermal therapy. In this study, the thermal lens technique was introduced to assess the optically induced temperature changes in colloidal samples of gold nanoparticles. Thermal lens measurements also allowed the acquisition of the nanoparticle absorption cross-section value, regardless of knowing the nanostructure scattering properties. The developed thermometric system exhibited 0.2 °C−1 sensitivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…We can now study Equation (7) or its analogous Equation (5) using the correct values for the maximum and the minimum. We have used a nonlinear least squares routine to fit the temporal behavior at these positions obtained with the exact numerical simulation as if they were experimental acquisitions.…”
Section: Results Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…We can now study Equation (7) or its analogous Equation (5) using the correct values for the maximum and the minimum. We have used a nonlinear least squares routine to fit the temporal behavior at these positions obtained with the exact numerical simulation as if they were experimental acquisitions.…”
Section: Results Comparisonmentioning
confidence: 99%
“…Indeed, as already mentioned, Equation ( 6) is obtained following a rather rough calculation, so it is not surprising to see that its extremums also do not correspond exactly to the correct values that are obtained around V ≈ ±0.7, separated therefore by a distance ≈ √ 2. We can now study Equation (7) or its analogous Equation (5) using the correct values for the maximum and the minimum. We have used a nonlinear least squares routine to fit the temporal behavior at these positions obtained with the exact numerical simulation as if they were experimental acquisitions.…”
Section: Results Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest detectable concentrations he has reported were of 0.22 and 0.08 μM of the compound for distilled and tap water, respectively. Pedrosa et al [97] have shown that using TLS, it is possible to measure temperature variations of 0.01 °C, at least in case of the gold-nanoparticle they studied dissolved in water. Recently, Sebastian et al [98] have shown that using TLS, it is possible to estimate the porosity of a nanomaterial composed of nano-particles.…”
Section: Advances In Tlm and Tlsmentioning
confidence: 99%
“…Moreover, Z-scan [ 10 ] based methods were performed at different regimes of excitation to understand the origin of the third-order nonlinear optical response [ 11 ] and the influence of the accumulated thermal effect, which can be an artifact in femtosecond closed-aperture Z-scan measurements [ 12 ]. Additionally, they can be used to evaluate optically-induced temperature changes in colloidal samples for photothermal therapy [ 13 ]. Already, we have experimentally demonstrated the feasibility of extracting an image of the phase shift induced by TL and applied this method to transversally map an inhomogeneous thin film doped with different concentrations of silver nanoparticles [ 14 ].…”
Section: Introductionmentioning
confidence: 99%